Secukinumab in Active Rheumatoid Arthritis: A Phase III Randomized, Double‐Blind, Active Comparator– and Placebo‐Controlled Study. Issue 6 (3rd May 2017) - Blanco, Francisco J.; Möricke, Rüdiger; Dokoupilova, Eva; Codding, Christine; Neal, Jeffrey; Andersson, Mats; Rohrer, Susanne; Richards, Hanno
Abstract : Objective: To evaluate the efficacy and safety of secukinumab in patients with active rheumatoid arthritis (RA) who had an inadequate response to or intolerance of tumor necrosis factor (TNF) inhibitors. Methods: In this phase III study, 551 patients were randomized (1:1:1:1) to receive intravenous secukinumab at a dose of 10 mg/kg (at baseline and weeks 2 and 4) followed by subcutaneous secukinumab at a dose of either 150 mg or 75 mg every 4 weeks or, alternatively, abatacept or placebo on the same dosing schedule. The primary end point was the proportion of patients achieving 20% improvement in disease activity according to the American College of Rheumatology response criteria (ACR20) at week 24 in the secukinumab 150 mg or 75 mg treatment groups as compared with placebo. Key secondary end points included change from baseline to week 24 in the Disease Activity Score in 28 joints using C‐reactive protein level (DAS28‐CRP) and the Health Assessment Questionnaire disability index (HAQ DI), as well as the ACR 50% improvement (ACR50) response rate at week 24. Results: The primary efficacy end point was met in patients receiving 150 mg secukinumab, in whom the ACR20 response rate at week 24 was significantly higher than that in the placebo group. The ACR20 response rates at week 24 were 30.7% in patients receiving 150 mg secukinumab ( P = 0.0305), 28.3% in those receiving 75 mg secukinumab ( P = 0.0916), and 42.8% in those receiving abatacept, compared with 18.1% in the placebo group. A significant reduction in the DAS28‐CRP was seen in patients treated with 150 mg secukinumab ( P = 0.0495), but not in patients treated with 75 mg secukinumab. Improvements in the HAQ DI and ACR50 response rates were not significant in the 2 secukinumab dose groups compared with the placebo group. The overall safety profile was similar across all treatment groups. Conclusion: Secukinumab at a dose of 150 mg resulted in improvement in signs and symptoms and reduced disease activity in patients with active RA who had an inadequate response to TNF inhibitors. Improvements observed with abatacept were numerically higher than with secukinumab. There were no new or unexpected safety signals with secukinumab in this study.